ANALISIS SARANG LEBAH MADU DALAM GEOMETRI MATEMATIKA DAN ALQURAN - Cindy Dwi Novitasari; Bambang Sri Anggoro; Komarudin Komarudin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
The purpose of this study was to obtain scientific evidence about the features of honey bee hives in two aspects, namely mathematical geometry, and the Qur'an. The research method used is qualitative research. Where research is conducted is library research by conducting content analysis with the conceptual realm. The process of data analysis is done with a preliminary study looking for references, followed by data collection, then conclusions will be drawn, then the data is validated in the form of triangulation methods. The results of the study show that hexagon is the optimal form when viewed in mathematical geometry because compared to other forms of hexagonal has the largest capacity area with a small circumference so that it requires little raw material for making nests. In addition, the hexagon is very possible in making the nest there is no gap between one cavity and the other cavity. Whereas reviewed in the Qur'an shows that the hexagon shape is very symmetrical and the selection of the nested form is inseparable from the intervention of Allah SWT, which Allah has given the miracle of being a bee in the form of revelation to create a nest with all its features.